Innovative Packaging Attributes and Customer Purchase Intention in Snack Foods - Song, Xiaokang; Syriac, Nellikunnel (INTI International University, 2018)
Packaging is now an important aspect of marketing and is treated as one of the most influential factors concerning consumer purchase decision at the point of purchase. The purpose of this study is to determine what kind of innovative packaging attributes will influence the purchase intention of customers on snack food in Malaysia. The study has used Stimulus (S) - Response (R) model and AIDA Model to identify the packaging attributes which are packaging material, information on the package and the basic appearance of the package that have a positive and strong relationship with the purchase intention of customers towards snack food. The data were collected through questionnaire from 250 respondents. PLS has been used to analysis the data. All of the three independent variables of the research have significant as well as positive relationship with the dependent variable which is purchase intention.